Strengthening and expanding health inequality monitoring for the advancement of health equity: a review of WHO resources and contributions - Ahmad Reza Hosseinpoor; Nicole Bergen; Katherine Kirkby; Anne Schlotheuber (BMC, 2023)
Abstract As part of its commitment to advance health equity, the World Health Organization (WHO) has a developed area of work to promote and strengthen health inequality monitoring. This includes an emphasis on the collection, analysis and use of disaggregated health data, which are central to evidence-informed decision making. The aim of this paper is to review WHO's work on health inequality monitoring, namely the 2022-27 Inequality monitoring and analysis strategy and corresponding activities, resources and tools. The strategy has three goals pertaining to: strengthening capacity for health inequality monitoring; generating and disseminating the latest evidence on health inequality and supporting data disaggregation; and developing and refining health inequality monitoring methods, resources and best practices. In alignment with these goals, WHO has published reference materials focused on conceptual approaches to health inequality monitoring, which are applied in the global State of Inequality report series. The Health Inequality Monitoring eLearning channel on OpenWHO and capacity building workshops and webinars facilitate the uptake and application of inequality monitoring practices across diverse settings and stakeholders. A key tool available to support the analysis and reporting aspects of health inequality monitoring is the Health Equity Assessment Toolkit (HEAT) application, which allows users to explore data interactively. The Health Inequality Data Repository, a collection of the largest publicly available database of disaggregated data from around the globe, further enables inequality monitoring and analyses. This collection of resources is an important contribution to promote health inequality monitoring across diverse settings. The uptake of evidence from health inequality monitoring remains crucial to the advancement of equity as part of global health and development initiatives.